Inorganic coated sand

By adding an appropriate amount of calcium compound to the inorganic binder layer of the inorganic coated sand, the problem of mold deformation at high temperatures is solved, and higher dimensional accuracy and mold strength are achieved.

CN114929410BActive Publication Date: 2025-01-14KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080092089.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-09
Filing Date
2020-10-26
Publication Date
2025-01-14
Estimated Expiration
2040-10-26

AI Technical Summary

Technical Problem

When manufacturing complex and thin-walled cast molds, existing inorganic coated sand is prone to deform under the action of high-temperature molten metal, resulting in poor dimensional accuracy.

Method used

By adding a calcium compound to the inorganic binder layer of the inorganic coated sand, ensuring that the Ca content is between 3% and below 45%, mold deformation is suppressed during casting.

Benefits of technology

It effectively suppresses the deformation of the mold at high temperatures and improves the dimensional accuracy and strength of the mold.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003730562630000211
    Figure BDA0003730562630000211
  • Figure BDA0003730562630000221
    Figure BDA0003730562630000221
  • Figure BDA0003730562630000231
    Figure BDA0003730562630000231
Patent Text Reader

Abstract

The inorganic coated sand of the present invention comprises a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is greater than 3% by mass and less than 45% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to inorganic coated sand. Background Art

[0002] As a casting mold for casting a casting, for example, a casting mold formed into a target shape using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate is known.

[0003] As technologies related to such inorganic coated sand, for example, there are technologies described in Patent Document 1 (Japanese Patent Publication No. 53-025803), Patent Document 2 (International Publication No. 2018 / 147419), and Patent Document 3 (International Publication No. 2018 / 097180).

[0004] Patent Document 1 describes a method for making a casting mold, wherein a metasilicate solution prepared by adding caustic soda to water glass is added to refractory particles such as silica sand and kneaded, or an alcohol is further added during the kneading, so that crystalline alkaline silicate is precipitated and attached to the surface of the refractory particles such as silica sand, and then the crystalline alkaline silicate is generated during the refining of Fe-Si and converted into SiO 2 The powdery mixed sand to which the fine dust as the main component is added and mixed is heated to at least the melting point of the above-mentioned crystalline alkaline silicate and solidified.

[0005] Patent Document 2 describes a casting material composition comprising at least a refractory aggregate, a binder including water glass as an essential component, and at least one nitrate selected from alkali metal salts and alkaline earth metal salts of nitric acid.

[0006] Patent document 3 describes a technology for coated sand, wherein the coated sand is dry coated sand having fluidity at room temperature, wherein the surface of a refractory aggregate is covered with a coating layer containing water glass, and the coating layer contains spherical particles.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Publication No. 53-025803

[0010] Patent Document 2: International Publication No. 2018 / 147419

[0011] Patent Document 3: International Publication No. 2018 / 097180 Summary of the invention

[0012] According to the present invention, there is provided a method for suppressing mold deformation, wherein:

[0013] In a casting mold made using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is set to be greater than 3% by mass and less than 45% by mass, thereby suppressing deformation of the casting mold during casting.

[0014] According to the present invention, an inorganic coated sand is provided.

[0015] The invention comprises a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate.

[0016] The inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, and the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is 3 mass % or more and 45 mass % or less. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a cross-sectional view for explaining the method of measuring deformation of a casting mold in Examples. DETAILED DESCRIPTION

[0018] Through research conducted by the present inventors, it has been newly discovered that, in the case of conventional inorganic coated sand, when a mold having a complex and thin-walled shape is produced, the mold is exposed to high-temperature molten metal during casting and deforms, and that there is room for improvement in dimensional accuracy.

[0019] The present invention provides a method for suppressing deformation of a mold produced using inorganic coated sand during casting. In addition, the present invention provides inorganic coated sand that suppresses deformation of the mold that occurs during casting.

[0020] The present inventors have found that in a mold produced using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, deformation of the mold during casting can be suppressed by containing a calcium compound in the inorganic binder layer.

[0021] According to the present invention, a method for suppressing deformation of a mold produced using inorganic coated sand during casting can be provided. In addition, according to the present invention, inorganic coated sand that suppresses deformation of a mold during casting can be provided.

[0022] The following is an explanation of the embodiments of the present invention. In addition, in this specification, unless otherwise specified, "A to B" indicating a numerical range indicates a range of greater than A and less than B, including both ends. In addition, the components / elements described in each embodiment can be appropriately combined within the scope of not impairing the effect of the invention.

[0023] <Method for suppressing deformation of the mold during casting>

[0024] In the present embodiment, regarding a method for suppressing mold deformation during casting, in a mold made using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, and the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is set to be greater than 3 mass % and less than 45 mass %.

[0025] (Mechanism of suppressing deformation)

[0026] Specifically, in this embodiment, the inorganic binder layer of the inorganic coated sand contains a specific amount of calcium compound, and the heat of the molten metal is used during casting to react sodium silicate or sodium metasilicate with calcium to crystallize into Na 2 O·CaO·SiO 2 The high melting point crystal of the ternary system. The high melting point crystal does not melt even when exposed to the heat of the molten metal, and thus can effectively suppress the deformation of the mold. The inventors of the present invention have newly discovered that by using the inorganic coated sand to make a mold, the deformation of the mold can be suppressed.

[0027] Hereinafter, the method for producing the inorganic coated sand and the casting mold will be described in more detail.

[0028] <Inorganic coated sand>

[0029] The inorganic coated sand has a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate. The inorganic binder contains at least one selected from sodium silicate and sodium metasilicate. The inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is 3 mass % or more and 45 mass % or less.

[0030] Specifically, the inorganic coated sand is composed of a group of particles of inorganic coated sand, and specifically, the refractory aggregate is composed of a group of particles of refractory aggregate.

[0031] The inorganic coated sand is preferably spherical from the viewpoint of improving fluidity and further improving the filling property in the molding die. Here, the inorganic coated sand being spherical means having a round shape such as a sphere.

[0032] More specifically, from the viewpoints of fluidity, improvement of mold quality and mold strength, and ease of mold shaping, the sphericity of the inorganic coated sand is preferably 0.80 or more, more preferably 0.85 or more, further preferably 0.90 or more, further more preferably 0.95 or more, and particularly preferably 0.97 or more. In addition, the upper limit of the sphericity is specifically 1 or less.

[0033] Here, the sphericity of the inorganic coated sand can be obtained by the following method: by analyzing the image (photograph) of the particles obtained using an optical microscope or a digital oscilloscope (for example, VH-8000 manufactured by KEYENCE), the area of ​​the particle projected cross section and the perimeter of the cross section of the particles are obtained, and then the ratio of the area of ​​the particle projected cross section (mm) is calculated. 2 )〔circumference of a perfect circle of equal area (mm)〕 / 〔circumference of a particle projected cross section (mm)〕, and the average of the values ​​obtained for any 50 particles is calculated.

[0034] From the viewpoint of improving the quality and strength of the mold and the ease of molding the mold, the average particle size of the inorganic coated sand is preferably 0.05 mm or more, and more preferably 0.1 mm or more. In addition, if the average particle size of the inorganic coated sand is greater than the above lower limit, the amount of the inorganic binder layer can be reduced when manufacturing the mold, which is also preferred from the perspective of easier regeneration of the inorganic coated sand.

[0035] From the viewpoint of improving the quality and strength of the mold and the ease of molding the mold, the average particle size of the inorganic coated sand is preferably 2 mm or less, more preferably 1 mm or less, and further preferably 0.5 mm or less. In addition, if the average particle size of the inorganic coated sand is below the above upper limit, the porosity becomes small when manufacturing the mold, which is also preferred from the perspective of improving the strength of the mold.

[0036] In the present embodiment, the average particle size of the inorganic coated sand and the refractory aggregate described later can be specifically measured by the following method.

[0037] (Method for measuring average particle size)

[0038] The diameter (mm) is measured based on the case where the sphericity of the particle projection cross section of the particle is 1. On the other hand, when the sphericity is <1, the major axis diameter (mm) and the minor axis diameter (mm) of the randomly oriented particles are measured and (major axis diameter + minor axis diameter) / 2 are calculated. For any 100 particles, the values ​​obtained are averaged as the average particle diameter (mm). The major axis diameter and the minor axis diameter are defined as shown below. The particle is stabilized on a plane. When the projection image of the particle on the plane is sandwiched by two parallel lines, the width of the particle when the interval between the parallel lines is the smallest is called the minor axis diameter. On the other hand, the distance when the particle is sandwiched by two parallel lines perpendicular to the parallel lines is called the major axis diameter.

[0039] The major axis diameter and minor axis diameter of the particle can be obtained by taking an image (photograph) of the particle using an optical microscope or a digital oscilloscope (eg, VH-8000 manufactured by KEYENCE) and performing image analysis on the obtained image.

[0040] (Refractory Aggregate)

[0041] As a material of a refractory aggregate, one or more types selected from a natural sand and an artificial sand are mentioned.

[0042] Examples of the natural sand include one or more selected from silica sand containing quartz as a main component, chromite sand, zircon sand, olivine sand, and alumina sand.

[0043] As artificial sand, for example, synthetic mullite sand, SiO 2 SiO as the main component 2 Casting sand of Al 2 O 3 Al as the main component 2 O 3 Casting sand, SiO 2 / Al 2 O 3 Casting sand, SiO 2 / MgO-based casting sand, SiO 2 / Al 2 O 3 / ZrO 2 Casting sand, SiO 2 / Al 2 O 3 / Fe 2 O 3 One or more of the casting sand of the system and the casting sand derived from slag. Here, the main component refers to the component that is the largest among the components contained in the sand.

[0044] Artificial sand refers to casting sand that is not naturally produced, but is obtained by artificially preparing metal oxide components and melting or sintering them. In addition, recycled sand obtained by recycling used refractory aggregates, regenerated sand obtained by regenerating recycled sand, etc. can also be used.

[0045] From the viewpoint of improving the fluidity of the inorganic coated sand and further improving the filling property into the molding die, the refractory aggregate is preferably in a particle form.

[0046] In addition, from the viewpoint of improving the quality and strength of the mold and the ease of molding of the mold, the average particle size of the refractory aggregate is preferably 0.05 mm or more, and more preferably 0.1 mm or more. In addition, if the average particle size of the refractory aggregate is above the above lower limit, the amount of the inorganic binder layer can be reduced when manufacturing the mold, and therefore, it is also preferred from the aspect of easier regeneration of the inorganic coated sand.

[0047] From the viewpoint of improving mold quality and mold strength, the viewpoint of mold modeling ease, the average particle size of refractory aggregate is preferably below 2mm, more preferably below 1mm, further preferably below 0.5mm. In addition, if the average particle size of refractory aggregate is below the above-mentioned upper limit, then when manufacturing mold, void ratio decreases, and it is also preferred from the aspect of improving mold strength.

[0048] (Inorganic binder layer)

[0049] Specifically, the inorganic binder layer contains an inorganic binder and a calcium compound.

[0050] The so-called inorganic binder layer is a coating layer formed on the surface of the refractory aggregate, specifically, a layer obtained by mixing and coating an inorganic binder, a calcium compound, and a compound of a Na source and a Si source as required; a layer obtained by further coating a calcium compound and a compound of a Na source and a Si source as required on a layer obtained by mixing and coating an inorganic binder and at least one compound selected from a Na source and a Si source as required; or a layer obtained by mixing and coating an inorganic binder and a calcium compound and at least one compound selected from a Na source and a Si source as required, a layer obtained by further coating a calcium compound and at least one compound selected from a Na source and a Si source as required.

[0051] From the viewpoint of improving the casting strength, the content of the inorganic binder layer in the inorganic coated sand is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, further preferably 0.5 parts by mass or more, further more preferably 1 part by mass or more, and particularly preferably 2 parts by mass or more, relative to 100 parts by mass of the refractory aggregate.

[0052] In addition, from the viewpoint of improving the filling property into the forming mold and improving the casting strength, the content of the inorganic binder layer in the inorganic coated sand is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and further preferably 7 parts by mass or less, relative to 100 parts by mass of the refractory aggregate.

[0053] Here, the content of the inorganic binder layer refers to the content excluding water contained in the inorganic binder layer.

[0054] Next, components contained in the inorganic binder layer will be described.

[0055] (Inorganic binder)

[0056] In the present embodiment, the inorganic binder includes at least one selected from the group consisting of sodium silicate and sodium metasilicate from the viewpoint of excellent productivity and easy availability.

[0057] From the viewpoint of improving the productivity of the inorganic coated sand and the productivity of the mold, the inorganic binder preferably contains sodium metasilicate or a hydrate thereof, and more preferably contains sodium metasilicate hydrate.

[0058] In addition, the inorganic binder may also include an inorganic binder having a water-soluble silicic acid compound other than the above-mentioned sodium silicate and sodium metasilicate as a main component. Specific examples of silicic acid compounds other than sodium silicate and sodium metasilicate include potassium silicate, potassium metasilicate, lithium silicate, and ammonium silicate.

[0059] As sodium silicate, specifically, one or more selected from sodium silicate No. 1 to No. 5 can be mentioned. Here, sodium silicate is SiO 2 / Na 2 O molar ratio is classified into No. 1 to No. 5, and No. 1 to No. 3 sodium silicates are specified in JIS-K-1408. 2 / Na 2 The molar ratio of O is specifically as shown below.

[0060] Sodium silicate No. 1: SiO 2 / Na 2 O molar ratio = 2.0 to 2.3

[0061] Sodium silicate No. 2: SiO 2 / Na 2 O molar ratio = 2.4 to 2.6

[0062] Sodium silicate No. 3: SiO 2 / Na 2 O molar ratio = 2.8 to 3.3

[0063] Sodium silicate No. 4: SiO 2 / Na 2 O molar ratio = 3.3 to 3.5

[0064] Sodium silicate No. 5: SiO 2 / Na 2 O molar ratio = 3.6 to 3.8

[0065] In addition, by mixing two or more kinds of sodium silicates, SiO 2 / Na 2 The molar ratio of O is adjusted to a desired level.

[0066] From the viewpoint of improving the productivity of the inorganic coated sand and the viewpoint of improving the productivity of the casting mold, the sodium metasilicate is preferably a hydrate.

[0067] As the sodium metasilicate hydrate, from the above viewpoint, at least one selected from sodium metasilicate pentahydrate and sodium metasilicate nonahydrate is preferred.

[0068] From the viewpoint of improving the strength of the mold and making the surface shape of the mold good, the content of the inorganic binder in the inorganic binder layer is preferably 5% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further more preferably 18% by mass or more, and further more preferably 30% by mass or more, relative to the entire inorganic binder layer.

[0069] In addition, from the viewpoint of further suppressing the deformation of the casting at high temperature, the content of the inorganic binder in the inorganic binder layer is preferably 85 mass % or less, more preferably 70 mass % or less, further preferably 60 mass % or less, further more preferably 55 mass % or less, and further more preferably 48 mass % or less, relative to the entire inorganic binder layer.

[0070] Here, the content of the inorganic binder in the inorganic binder layer refers to the content of the inorganic binder excluding water relative to all components excluding water in the inorganic binder layer.

[0071] From the viewpoint of improving mold strength, the viewpoint of excellent productivity and the viewpoint of easy acquisition, the total content of sodium silicate and sodium metasilicate in the inorganic binder is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, further preferably 98 mass % or more, further preferably substantially 100 mass %. Here, "substantially" means that it may include unintentionally included components, such as components other than sodium silicate and sodium metasilicate contained in the sodium silicate and sodium metasilicate as raw materials.

[0072] The total content of sodium silicate and sodium metasilicate in the inorganic binder refers to the total content of sodium silicate and sodium metasilicate relative to all components except water in the inorganic binder.

[0073] (Calcium compounds)

[0074] From the viewpoint of suppressing deformation of a mold at high temperatures, the calcium compound preferably includes a Ca salt of an inorganic compound.

[0075] From the viewpoint of suppressing deformation of the casting mold at high temperature, the content of the Ca salt of the inorganic compound in the calcium compound is preferably 80% by mass or more, more preferably 90% by mass or more, further preferably 95% by mass or more, and further preferably 98% by mass or more. The upper limit of the content of the Ca salt of the inorganic compound in the calcium compound is 100% by mass.

[0076] It is believed that when the mold solidifies, the calcium compound dissolves in the sodium silicate or sodium metasilicate aqueous solution, and a portion of the dissolved calcium compound reacts with the sodium silicate or sodium metasilicate to increase the mold strength. Therefore, it is preferred that the calcium compound be soluble in water.

[0077] On the other hand, if the solubility in water is too high, the reaction between sodium silicate or sodium metasilicate and the calcium compound may proceed excessively, resulting in excessive formation of calcium silicate gel, which may inhibit liquid crosslinking by the inorganic binder and reduce the casting strength.

[0078] Therefore, from the viewpoint of improving the casting strength, the solubility of the calcium compound in water at 20°C is preferably 0.001 g / L or more, more preferably 0.005 g / L. From the same viewpoint, it is preferably 10 g / L or less, more preferably 5 g / L or less, further preferably 3 g / L or less, further preferably 1.5 g / L or less, further preferably 0.5 g / L or less, further preferably 0.1 g / L or less, further preferably 0.01 g / L or less.

[0079] The solubility of each calcium salt in water is calcium carbonate (0.015 g / L at 25°C), calcium silicate (0.01 g / L at 20°C), calcium oxide (1.19 g / L at 25°C), calcium sulfate (2.4 g / L at 20°C), and calcium sulfate (dihydrate) (2.1 g / L at 20°C).

[0080] Examples of the Ca salt of an inorganic compound include one or more Ca salts selected from the group consisting of calcium oxide, calcium carbonate, calcium silicate, calcium sulfate, calcium nitrate, and calcium phosphate.

[0081] From the viewpoint of suppressing deformation of a casting mold at a high temperature, the calcium compound is preferably at least one selected from calcium oxide and calcium carbonate, and more preferably calcium oxide.

[0082] From the viewpoint of improving mold strength, the calcium compound having lower water solubility is more preferred, more preferably at least one selected from calcium carbonate, calcium silicate and calcium oxide, and even more preferably at least one of calcium carbonate and calcium silicate.

[0083] Moreover, from the viewpoint of achieving both suppression of mold deformation at high temperatures and improvement of mold strength, calcium carbonate is preferred.

[0084] In addition, as another example of the calcium compound, there can be mentioned a compound containing calcium among the substances described later as other components contained in the inorganic binder layer.

[0085] From the viewpoint of suppressing deformation of the mold, the Ca content in the inorganic binder layer is 3 mass % or more, preferably 7 mass % or more, more preferably 15 mass % or more, and further preferably 16 mass % or more, relative to all components in the inorganic binder layer excluding water.

[0086] In addition, from the viewpoint of improving the casting strength, the Ca content in the inorganic binder layer is 45 mass % or less, preferably 40 mass % or less, more preferably 35 mass % or less, and further preferably 33 mass % or less, relative to all components in the inorganic binder layer except water.

[0087] A specific method for measuring the Ca content in the inorganic binder layer will be described later.

[0088] (Other additives)

[0089] In addition to the above-mentioned components, the inorganic binder layer may contain various additives as required. Other additives include humectants, moisture resistance enhancers, coupling agents for enhancing the bonding between the refractory aggregate and the inorganic binder, lubricants, surfactants, and the like.

[0090] Examples of the moisturizer include polyols, water-soluble polymers, hydrocarbons, sugars, proteins, and inorganic compounds other than the above. Among them, inorganic compounds preferably include calcium-containing inorganic compounds such as calcium chloride from the viewpoint of adjusting the calcium content.

[0091] Examples of the moisture resistance improving agent include metal oxides such as the aforementioned calcium oxide, carbonates such as the aforementioned calcium carbonate, borates such as calcium borate, sulfates such as the aforementioned calcium sulfate, and phosphates such as calcium phosphate.

[0092] Examples of the lubricant include waxes, fatty acid amides, alkylene fatty acid amides, stearic acid, stearyl alcohol, metal stearates such as lead stearate, zinc stearate, calcium stearate, and magnesium stearate, stearic acid monoglyceride, stearyl stearate, and hydrogenated oil.

[0093] Examples of the release agent include paraffin, wax, light oil, engine oil, spindle oil, insulating oil, waste oil, vegetable oil, fatty acid ester, organic acid, graphite particles, mica, vermiculite, fluorine-based release agents, and silicone-based release agents.

[0094] (Na:Ca:Si molar ratio)

[0095] From the viewpoint of suppressing deformation of the mold and improving the strength of the mold, the molar ratio of Na:Ca:Si in the inorganic binder layer is preferably 15 to 85:5 to 75:10 to 80, more preferably 15 to 77:13 to 75:10 to 72, further preferably 20 to 70:20 to 70:10 to 60, and still more preferably 22 to 62:28 to 68:10 to 50.

[0096] Here, the adjustment of the molar ratio of Na:Ca:Si can be realized by adjusting the content of the inorganic binder in the inorganic binder layer and the content of the calcium compound. In addition, in addition to the above-mentioned inorganic binder and calcium compound, the sodium compound as the Na source and the silicon compound as the Si source can be added to the inorganic binder layer to adjust the molar ratio. As a sodium compound, from the viewpoint of suppressing the deformation of the mold, it is preferably an inorganic sodium compound other than sodium silicate and sodium metasilicate, and specifically sodium compounds such as sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium oxide, sodium phosphate, sodium hydrogen phosphate, sodium sulfate, sodium tetraborate, sodium metaborate can be cited. As a silicon compound, from the viewpoint of suppressing the deformation of the mold, it is preferably an inorganic silicon compound other than sodium silicate and sodium metasilicate, and specifically silicon compounds such as amorphous silica (fused silica, fumed silica, precipitated silica, etc.), crystalline silica, ferrosilicon can be cited.

[0097] In addition, when the other additives include Ca, Na, and Si, the content thereof also includes the molar ratio of Na:Ca:Si in the inorganic binder layer.

[0098] From the viewpoint of improving the mold strength and the viewpoint of improving the moisture resistance of the mold, it is preferred that the inorganic binder layer also contains a silicon compound other than sodium silicate and sodium metasilicate. As the silicon compound, from the viewpoint of high reactivity with sodium silicate and sodium metasilicate, amorphous silicon dioxide is preferably used. Preferred examples of amorphous silicon dioxide are described later.

[0099] The molar ratio of Na:Ca:Si in the inorganic binder layer can be determined from, for example, the raw material composition used for producing the inorganic coated sand.

[0100] The molar ratio of Na:Ca:Si can be determined, for example, by analyzing inorganic coated sand. Specifically, it can be determined by the following method.

[0101] The inorganic coated sand is soaked in water or hot water to extract the inorganic binder layer, and the refractory aggregate is removed from the extract by filtration. The obtained eluate is dried to obtain an inorganic binder layer extract. The inorganic binder layer extract is subjected to fluorescent X-ray analysis under the following conditions to determine the Ca content and the Na:Ca:Si molar ratio in the inorganic binder layer.

[0102] That is, the inorganic binder layer extract was adjusted to less than 0.1 μm using a vibration mill and heated at 1050°C for 1 hour. Then, 5 g of lithium tetraborate and 0.5 g of the inorganic binder layer extract were mixed and heated at 1200°C for 10 minutes to melt them, and then cooled to prepare a glass-like sample (glass bead method). The sample was subjected to fluorescent X-ray analysis using a fluorescent X-ray analyzer ZSX Primus II (manufactured by Rigaku Corporation) using the Fundamental Parameter (FP) method. From the obtained Na 2 O, CaO, SiO 2 The Ca content and the Na:Ca:Si molar ratio were calculated based on the analysis results of the mass ratio.

[0103] Na 2 O, CaO and SiO 2 When the mass ratios of are a (wt%), b (wt%) and c (wt%), the Ca content and the Na:Ca:Si molar ratio can be calculated using the following formulae, respectively.

[0104] Ca content relative to 100 parts by mass of the inorganic binder layer: b×40.1 (Ca atomic weight) / 56.1 (CaO molecular weight)

[0105] Na:Ca:Si molar ratio

[0106] Na molar ratio = (a×2 / 62.0) / (a×2 / 62.0+b / 56.1+c / 60.1)

[0107] Ca molar ratio = (b / 56.1) / (a×2 / 62.0+b / 56.1+c / 60.1)

[0108] Si molar ratio = (c / 60.1) / (a×2 / 62.0+b / 56.1+c / 60.1)

[0109] (Amorphous silicon dioxide)

[0110] As the amorphous silica, amorphous silica particles are preferred because they have a large specific surface area and high reactivity with sodium silicate or sodium metasilicate.

[0111] From the viewpoint of making the inorganic coated sand particles more firmly bonded to each other by the amorphous silica particles, the amorphous degree of the amorphous silica particles is preferably 80% or more, more preferably 90% or more, further preferably 93% or more, further more preferably 95% or more, and particularly more preferably 98% or more. The upper limit of the amorphous degree of the amorphous silica particles is not limited, for example, it is 100% or less, it can be 99.8% or less, and it can be 99% or less.

[0112] From the viewpoint of improving the mold strength per unit mass and handling properties, the average particle size d in the weight-based particle size distribution of the amorphous silica particles by laser diffraction scattering particle size distribution measurement method is 2.5-3.5 mm / s. 50 It is preferably 0.1 μm or more, and more preferably 0.3 μm or more. In order to improve the mold strength per unit mass, the average particle size d of the amorphous silica particles is preferably 0.1 μm or more, and more preferably 0.3 μm or more. 50 It is preferably 2.0 μm or less, more preferably 1.0 μm or less, further preferably 0.8 μm or less, and further more preferably 0.6 μm or less.

[0113] Here, the average particle size d in the weight-based particle size distribution of the amorphous silica particles by laser diffraction scattering particle size distribution measurement method is 50 For example, the amorphous silica particles can be obtained by dissolving the inorganic binder layer with water and removing it from the inorganic coated sand, and then measuring the particle size of the obtained amorphous silica particles by laser diffraction scattering particle size distribution measurement.

[0114] The average particle size d in the weight-based particle size distribution of the amorphous silica particles by laser diffraction scattering particle size distribution measurement method is 50 It can also be obtained by measuring the particle size of amorphous silica particles as a raw material using a laser diffraction scattering particle size distribution measurement method.

[0115] In addition, from the viewpoint of improving the mold strength per unit mass and handling properties, the average particle size of the amorphous silica particles obtained from the image observed by a scanning electron microscope is preferably 0.1 μm or more, and more preferably 0.3 μm or more. In addition, from the viewpoint of improving the mold strength per unit mass, the average particle size of the amorphous silica particles obtained from the image observed by a scanning electron microscope is preferably 2.0 μm or less, more preferably 1.0 μm or less, further preferably 0.8 μm or less, and further more preferably 0.6 μm or less.

[0116] Here, the average particle size of the amorphous silicon dioxide particles obtained by the observation image of the scanning electron microscope can use various image analysis methods. As pre-treatment, irregular particle sorting can be carried out. For example, it is possible to determine the inorganic binder layer and the amorphous silicon dioxide particles according to the element, select 100 arbitrary amorphous silicon dioxide particles, measure their particle size, count 10 from the maximum particle size and count 10 from the minimum particle size, and use the average value of the particle size of 80 amorphous silicon dioxide particles except the total 20 amorphous silicon dioxide particles as the average particle size of amorphous silicon dioxide particles.

[0117] From the viewpoint of obtaining a high-strength mold, the water content in the inorganic binder layer contained in the inorganic coated sand is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of the inorganic binder.

[0118] In addition, from the perspective of filling the forming mold and obtaining a high-strength casting, the water content in the inorganic binder layer contained in the inorganic coated sand is preferably 180 parts by mass or less, more preferably 160 parts by mass or less, further preferably 150 parts by mass or less, and further preferably 140 parts by mass or less, relative to 100 parts by mass of the inorganic binder.

[0119] The water content in the inorganic binder layer included in the inorganic coated sand can be adjusted according to the type of the inorganic binder.

[0120] When the inorganic binder is sodium silicate, the water content in the inorganic binder layer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, based on 100 parts by mass of sodium silicate, from the viewpoint of obtaining a high-strength casting mold.

[0121] From the viewpoint of filling properties into a mold and obtaining a high-strength mold, the water content in the inorganic binder layer contained in the inorganic coated sand is preferably 55 parts by mass, preferably 50 parts by mass or less, based on 100 parts by mass of sodium silicate.

[0122] When the inorganic binder is sodium metasilicate, from the viewpoint of obtaining a high-strength casting mold and the viewpoint of simply manufacturing a casting mold, the content of water in the inorganic binder layer is preferably 60 mass parts or more, more preferably 65 mass parts or more, further preferably 90 mass parts or more, and further preferably 110 mass parts or more, relative to 100 mass parts of sodium metasilicate. In addition, from the viewpoint of making fluidity good and further improving the fillability of the forming mold, it is preferably 180 mass parts or less, more preferably 160 mass parts or less, further preferably 150 mass parts or less, and further preferably 140 mass parts or less.

[0123] For example, when the inorganic binder constituting the inorganic binder layer is only sodium metasilicate pentahydrate, the water content is 74 parts by mass relative to 100 parts by mass of sodium metasilicate. When the inorganic binder constituting the inorganic binder layer is only sodium metasilicate nonahydrate, the water content is 133 parts by mass relative to 100 parts by mass of sodium metasilicate.

[0124] <Method for producing inorganic coated sand>

[0125] The method for producing the inorganic coated sand can be selected according to the type of the inorganic binder, for example.

[0126] When the inorganic binder includes sodium silicate, for example, a water glass aqueous solution as an inorganic binder and an additive as required are kneaded or mixed together with the heated refractory aggregate and uniformly mixed, the surface of the refractory aggregate is coated with the water glass aqueous solution, and the water content of the water glass aqueous solution is evaporated, thereby obtaining dry inorganic coated sand having fluidity at room temperature.

[0127] When the inorganic binder contains sodium metasilicate hydrate, dry inorganic coated sand can be obtained, for example, by the following manufacturing method, which includes: a process of mixing refractory aggregate and sodium metasilicate hydrate at a temperature above the melting point of sodium metasilicate hydrate to obtain a mixture; and a process of cooling the mixture to a temperature lower than the melting point of sodium metasilicate hydrate.

[0128] According to this manufacturing method, the inorganic binder layer can be crystallized, so inorganic coated sand with excellent fluidity can be obtained compared with the existing manufacturing method. In addition, since there is no need to use an aqueous solution of sodium metasilicate hydrate, there is no need for a dehydration step, and the manufacturing method of the inorganic coated sand can be simplified.

[0129] In the step of obtaining the mixture, specifically, the fluidized sodium metasilicate hydrate is coated on the surface of the refractory aggregate at a temperature equal to or higher than the melting point of the sodium metasilicate hydrate.

[0130] As a method for mixing refractory aggregate and sodium metasilicate hydrate at a temperature above the melting point of sodium metasilicate hydrate, for example, there can be mentioned a method of adding sodium metasilicate hydrate to refractory aggregate heated to a temperature above the melting point of sodium metasilicate hydrate, and mixing the refractory aggregate and sodium metasilicate hydrate while melting the sodium metasilicate hydrate; and a method of adding heated and melted sodium metasilicate hydrate to refractory aggregate and mixing.

[0131] Among the above methods, the method of adding heated and melted sodium metasilicate hydrate to the refractory aggregate and mixing them is preferred from the viewpoint of being able to shorten the coating time.

[0132] From the same viewpoint, in the step of obtaining the mixture, it is preferred that the sodium metasilicate hydrate is mixed without previously preparing an aqueous solution. Furthermore, the step of obtaining the mixture preferably does not include a step of intentionally adding water.

[0133] The mixing conditions such as the stirring speed and the processing time when mixing the refractory aggregate and the sodium metasilicate hydrate can be appropriately determined according to the processing amount of the mixture.

[0134] In the step of cooling the mixture, the mixture obtained in the step of obtaining the mixture is cooled to a temperature lower than the melting point of sodium metasilicate hydrate, thereby reducing the fluidity of sodium metasilicate hydrate and fixing sodium metasilicate hydrate to the surface of the refractory aggregate, thereby forming a sodium metasilicate hydrate layer, i.e., an inorganic binder layer.

[0135] In addition, in the manufacture of inorganic coated sand, there is no limitation on the method of adding calcium compounds. For example, after coating the refractory aggregate with an inorganic binder, the above-mentioned other additives as needed, a Na source compound, and a Si source compound, the calcium compound, the other additives as needed, the Na source compound, and the Si source compound can be coated.

[0136] Alternatively, the refractory aggregate may be coated with an inorganic binder and a calcium compound, other additives as required, a compound of a Na source, and a compound of a Si source.

[0137] Alternatively, the inorganic binder and the calcium compound, other additives as needed, the compound of the Na source, and the compound of the Si source may be coated on the refractory aggregate together, and then the calcium compound, other additives as needed, the compound of the Na source, and the compound of the Si source may be coated.

[0138] The calcium compound can be prepared in a solid state, or in an aqueous solution or dispersion and mixed with a refractory aggregate, an inorganic binder, and the like.

[0139] The calcium compound may be added all at once or in multiple additions.

[0140] When the calcium compound is mixed in a solid state, from the viewpoint of improving the reactivity with the inorganic binder, the calcium compound is preferably a microparticle, and more preferably the average particle size of the calcium compound is 100 μm or less, further preferably 50 μm or less, and further more preferably 30 μm or less. In addition, from the viewpoint of easy handling and availability, the average particle size of the calcium compound is preferably 0.1 μm or more, and more preferably 0.5 μm or more.

[0141] The average particle size of the calcium compound can be specifically measured by the following measurement method.

[0142] (Method for measuring average particle size)

[0143] The volume cumulative 50% average particle size was measured using a laser diffraction particle size distribution analyzer LA-960V2 (manufactured by Horiba, Ltd.) The analysis conditions are as follows.

[0144] ·Determination method: Flow method

[0145] Dispersion medium: methanol

[0146] Dispersion method: stirring, built-in ultrasonic for 3 minutes

[0147] Sample concentration: 2mg / 100cc

[0148] Refractive index: Refractive index of each calcium compound (calcium carbonate: 1.580, calcium oxide: 1.830, calcium sulfate: 1.520, calcium silicate: 1.615)

[0149] The inorganic coated sand according to this embodiment can be obtained by the above method.

[0150] In addition, the obtained inorganic coated sand can be used alone or in combination with other known refractory aggregates and other additives to form a desired casting mold.

[0151] <Casting>

[0152] In this embodiment, the inorganic coated sand in the embodiment is used to make a mold. As a molding method for the mold, there are a molding method using a heated forming mold, a molding method in which water vapor is further introduced into the heated forming mold and then hot air is introduced.

[0153] When the inorganic binder layer contains sodium metasilicate hydrate, it is preferred to fill the inorganic coated sand into a heated forming mold and shape it. When the inorganic binder layer contains sodium silicate, it is preferred to add water to the inorganic coated sand, knead it, and then fill it into a heated forming mold and shape it; or fill the inorganic coated sand into a heated forming mold, pass water vapor, and then pass hot air to shape it.

[0154] When the inorganic binder layer contains sodium metasilicate hydrate, in a molding method using a heated molding die, for example, first, inorganic coated sand is filled in a molding die that provides a target casting.

[0155] Here, from the viewpoint of improving mold productivity, it is preferred to heat the forming mold by preheating before filling the inorganic coated sand. From the viewpoint of improving mold productivity and improving mold strength, the heating temperature at this time is preferably 100°C or more, more preferably 150°C or more, and preferably 300°C or less, more preferably 250°C or less.

[0156] After the inorganic coated sand is filled, the forming mold is heated without passing water vapor to solidify the inorganic coated sand. When the inorganic binder layer contains sodium metasilicate hydrate, the inorganic coated sand can be solidified without using a process of adding water to the inorganic coated sand and kneading it or a process of passing water vapor, so there is no need for equipment for passing water vapor.

[0157] From the viewpoint of improving mold productivity and mold strength, the heating temperature is preferably 100° C. or higher, more preferably 150° C. or higher, and preferably 300° C. or lower, more preferably 250° C. or lower. From the viewpoint of obtaining stable mold strength, the heating time is preferably 30 seconds or higher, more preferably 60 seconds or higher, and preferably 600 seconds or lower.

[0158] In addition, when the inorganic binder layer contains sodium silicate, water is added to the inorganic coated sand and kneaded, and then filled into a heated forming mold. In addition, in the molding method of passing water vapor, for example, after the inorganic coated sand is filled into the forming mold providing the target casting, water vapor is blown in. By passing water vapor, the filling phase of the inorganic coated sand is moistened and becomes a wet state. Then, hot air is passed into the forming mold heated to 90 to 200° C. to dry and solidify the inorganic coated sand.

[0159] In addition, the inorganic coated sand in this embodiment can also be used for the stacking molding method.

[0160] As mentioned above, although embodiment of this invention was described, the above-mentioned content is an illustration of this invention, and various structures other than the above-mentioned can also be adopted.

[0161] <1> A method for suppressing mold deformation, wherein in a mold made using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is set to 3% by mass or more and 45% by mass, thereby suppressing the mold deformation during casting.

[0162] <2> according to <1> The method for suppressing deformation of the mold during casting, wherein, in a mold made using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the content of the inorganic binder layer is 0.05 mass parts or more and 10 mass parts or less relative to 100 mass parts of the refractory aggregate in the inorganic coated sand, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, the inorganic binder layer contains a calcium compound, the Ca content in the inorganic binder layer is set to 3 mass % or more and 45 mass %, and the molar ratio of Na:Ca:Si in the inorganic binder layer is 15-85:5-75:10-80.

[0163] <3> according to <1> or <2> The method for suppressing mold deformation, wherein the total content of sodium silicate and sodium metasilicate in the inorganic binder is 80% by mass or more.

[0164] <4> according to <1> to <4> The method for suppressing mold deformation described in any one of the above aspects, wherein the calcium compound contains a Ca salt of an inorganic compound.

[0165] <5> according to <4> The method for suppressing mold deformation, wherein the content of the Ca salt of the inorganic compound in the calcium compound is 80% by mass or more.

[0166] <6> according to <1> to <5> The method for suppressing mold deformation according to any one of the preceding claims, wherein the solubility of the calcium compound in water at 20° C. is 0.001 g / L or more and 10 g / L or less.

[0167] <7> An inorganic coated sand, comprising a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, wherein the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, and the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is greater than 3% by mass and less than 45% by mass.

[0168] <8> according to <7> The inorganic coated sand comprises a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate. The content of the inorganic binder layer is greater than 0.05 parts by mass and less than 10 parts by mass relative to 100 parts by mass of the refractory aggregate in the inorganic coated sand. The inorganic binder contains at least one selected from sodium silicate and sodium metasilicate. The inorganic binder layer contains a calcium compound. The Ca content in the inorganic binder layer is greater than 3% by mass and less than 45% by mass. The molar ratio of Na:Ca:Si in the inorganic binder layer is 15-85:5-75:10-80.

[0169] <9> according to <7> or <8> The inorganic coated sand, wherein the total content of sodium silicate and sodium metasilicate in the inorganic binder is 80 mass % or more.

[0170] <10> according to <7> to <9> The inorganic coated sand according to any one of the preceding claims, wherein the calcium compound contains a Ca salt of an inorganic compound.

[0171] <11> according to <10> The inorganic coated sand, wherein the content of the Ca salt of the inorganic compound in the calcium compound is 80 mass % or more.

[0172] <12> according to <7> to <11> The inorganic coated sand according to any one of the preceding claims, wherein the solubility of the calcium compound in water at 20° C. is 0.001 g / L or more and 10 g / L or less.

[0173] Example

[0174] Hereinafter, the present invention will be described by way of Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples.

[0175] First, raw materials used in the following examples are shown.

[0176] (Raw materials for making inorganic coated sand)

[0177] Refractory aggregate

[0178] ESPEARL#60L (manufactured by Yamakawa Sangyo Co., Ltd., artificial alumina sand, average particle size: 241 μm)

[0179] Mikawa silica sand R6 (manufactured by Mikawa Silica Co., Ltd., average particle size: 200 μm)

[0180] Inorganic binder

[0181] Sodium metasilicate 9hydrate (Na 2 SiO 3 9H 2 O) (Made in Japan by Nippon Chemical Industry Co., Ltd.)

[0182] No. 1 50 water glass (SiO 2 / Na 2 O=2.1) (manufactured by Fuji Chemical Co., Ltd.)

[0183] Amorphous silica particles

[0184] Denka fused silica SFP-20M (average particle size d 50 : 0.4 μm, amorphization degree: 99.5 mass % or more) (manufactured by Denka)

[0185] Calcium salt

[0186] Calcium carbonate (CaCO 3 ) (Made by Fujifilm Wako Pure Chemical Industries, Ltd., powder, average particle size 6 μm)

[0187] Calcium oxide (CaO) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., powder, average particle size 19 μm)

[0188] Calcium sulfate (dihydrate) (CaSO 4 ·2H 2 O) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., powder, average particle size 38 μm)

[0189] Calcium silicate (CaSiO 3 ) (Made by Fujifilm Wako Pure Chemical Industries, Ltd., powder, average particle size 11 μm)

[0190] ·Sodium carbonate (anhydrous) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0191] <Examples 1 and 2>

[0192] ESPEARL#60L (100 parts by mass) was added to the mixer as a refractory aggregate. Next, sodium metasilicate 9hydrate (the amount shown in Table 1) heated to 80°C and melted was added to the mixer and kneaded for 4 minutes. Furthermore, calcium carbonate (the amount shown in Table 1) was added and kneaded for 2 minutes to obtain the inorganic coated sand of Examples 1 and 2. Table 1 shows the blending composition of the inorganic coated sand.

[0193] <Examples 3 to 18>

[0194] ESPEARL#60L (100 parts by mass) or Mikawa silica sand R6 (100 parts by mass) was added to a mixer as a refractory aggregate. Next, sodium metasilicate 9hydrate (the amount shown in Table 2) heated to 80°C and melted was added to a mixer and kneaded for 4 minutes, and then at least one of amorphous silica particles and sodium carbonate in the amounts shown in Table 2 was added and kneaded for 2 minutes. Next, a calcium salt in the amount shown in Table 2 was added and kneaded for 2 minutes to obtain the inorganic coated sand of Examples 3 to 18. Table 2 shows the composition of the inorganic coated sand of each example.

[0195] <Example 19>

[0196] ESPEARL#60L (100 parts by mass) heated to about 120°C was added to the mixer as a refractory aggregate. Next, No. 1 50 water glass (2 parts by mass) was added to the mixer and kneaded to evaporate the water, and the mixture was stirred for about 3 minutes until the sand particles collapsed. Furthermore, calcium carbonate (0.78 parts by mass) was added and kneaded for 2 minutes to obtain the inorganic coated sand of Example 19. Table 3 shows the composition of the inorganic coated sand.

[0197] <Comparative Example 1>

[0198] Except for not adding calcium carbonate, the same procedure as in Example 1 was carried out to obtain inorganic coated sand of Comparative Example 1. Table 1 shows the blending composition of the inorganic coated sand.

[0199] <Comparative Example 2>

[0200] Except for not adding calcium carbonate, the same procedure as in Example 3 was carried out to obtain inorganic coated sand of Comparative Example 2. Table 2 shows the blending composition of the inorganic coated sand.

[0201] <Comparative Example 3>

[0202] Except not adding calcium carbonate, the same procedure as in Example 15 was carried out to obtain inorganic coated sand of Comparative Example 3. Table 2 shows the blending composition of the inorganic coated sand.

[0203] <Comparative Example 4>

[0204] Except not adding calcium carbonate, the same procedure as in Example 19 was carried out to obtain inorganic coated sand of Comparative Example 4. Table 3 shows the blending composition of the inorganic coated sand.

[0205] (Evaluation method)

[0206] Using the inorganic coated sand obtained in each example, a casting mold was prepared by the following method, and its deformation was evaluated. The evaluation results are shown in each table.

[0207] (Making of casting mold)

[0208] <Examples 1 to 18, Comparative Examples 1 to 3>

[0209] The mold of the 22.3×22.3×180 mm test piece (5 pieces) was heated to 200° C. The inorganic coated sand of each example was filled with the inorganic coated sand at a blow molding pressure of 0.45 MPa using a CSR-43 blow molding machine. Then, the inorganic coated sand was left to stand in the molding mold for 2 minutes to solidify, thereby obtaining a casting test piece.

[0210] <Example 19, Comparative Example 4>

[0211] Water (1 part by mass) was added to inorganic coated sand (100 parts by mass) and kneaded for 2 minutes, and then the inorganic coated sand was filled into a mold in the same manner as in Examples 1 to 18 and Comparative Examples 1 to 3 to obtain a casting test piece.

[0212] (Deformation of the mold)

[0213] Figure 1 (a) and Figure 1 (b) is a cross-sectional view for illustrating the method of measuring mold deformation. After placing the mold test pieces of each example obtained by the above method in a constant temperature chamber at 25°C / 55%RH for 1 hour, a plate-shaped test piece 10 of 5×22.3×90 mm was cut out. Metal bases 11a and 11b (13 mm×13 mm, height 13 mm) were arranged on an iron plate of appropriate size so that the center distance was 90 mm, and the plate-shaped test piece 10 ( Figure 1 (a)). Furthermore, a weight 13 (4.7 g) is placed at the center of the plate-like test piece 10. Then, the iron plate on which the plate-like test piece 10 is placed is heated in a muffle furnace heated under the following conditions. After a predetermined time, the plate-like test piece 10 is taken out of the muffle furnace and left to cool for 1 hour. Then, the deformation amount of the plate-like test piece 10 is measured. The maximum vertical distance from the straight line connecting the two ends of the plate-like test piece 10 to the bent portion is taken as the deformation amount ( Figure 1 (b)).

[0214] (Heating conditions)

[0215] Examples 1-2, Comparative Example 1: 1000°C, 10 minutes

[0216] Examples 3 to 18, Comparative Examples 2 to 3: 700°C, 10 minutes

[0217] Example 19, Comparative Example 4: 700°C, 5 minutes

[0218] [Table 1]

[0219]

[0220] [Table 2]

[0221] [Table 3]

[0222]

[0223] According to Tables 1 to 3, in each of the Examples, the effect of suppressing mold deformation is superior to that of the Comparative Example.

[0224] Description of Reference Numerals

[0225] 10 Plate test piece

[0226] 11a, 11b Base

[0227] 13 Heavy Objects

Claims

1. A method for suppressing mold deformation, wherein: In a casting mold produced using inorganic coated sand having a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, the inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is set to 3% by mass or more and 45% by mass or less relative to all components in the inorganic binder layer except water, thereby suppressing deformation of the casting mold during casting, The calcium compound contains a Ca salt of an inorganic compound, The Ca salt of the inorganic compound is one or more Ca salts selected from the group consisting of calcium oxide, calcium carbonate, calcium silicate, calcium sulfate, calcium nitrate and calcium phosphate.

2. The method for suppressing mold deformation according to claim 1, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 15-85:5-75:10-80.

3. The method for suppressing mold deformation according to claim 1 or 2, wherein: The total content of the sodium silicate and the sodium metasilicate in the inorganic binder is 80 mass % or more.

4. The method for suppressing mold deformation according to claim 1 or 2, wherein: The content of the Ca salt of the inorganic compound in the calcium compound is 80% by mass or more.

5. The method for suppressing mold deformation according to claim 1 or 2, wherein: The solubility of the calcium compound in water at 20° C. is 0.001 g / L or more and 10 g / L or less.

6. The method for suppressing mold deformation according to claim 1 or 2, wherein: The content of the inorganic binder layer is 0.05 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the refractory aggregate in the inorganic coated sand.

7. The method for suppressing mold deformation according to claim 1 or 2, wherein: The Ca content in the inorganic binder layer is 3% by mass or more and 35% by mass or less relative to all components excluding water in the inorganic binder layer.

8. The method for suppressing mold deformation according to claim 1 or 2, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 15-77:13-75:10-72.

9. The method for suppressing mold deformation according to claim 1 or 2, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 20-70:20-70:10-60.

10. The method for suppressing mold deformation according to claim 1 or 2, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 22-62:28-68:10-50.

11. The method for suppressing mold deformation according to claim 1 or 2, wherein: The total content of the sodium silicate and the sodium metasilicate in the inorganic binder is 95% by mass or more.

12. The method for suppressing mold deformation according to claim 1 or 2, wherein: The calcium compound is one or more selected from the group consisting of calcium oxide, calcium carbonate, calcium silicate, calcium sulfate, calcium nitrate and calcium phosphate.

13. The method for suppressing mold deformation according to claim 1 or 2, wherein: The content of the Ca salt of the inorganic compound in the calcium compound is 95% by mass or more.

14. The method for suppressing mold deformation according to claim 1 or 2, wherein: The solubility of the calcium compound in water at 20° C. is 0.005 g / L or more and 3 g / L or less.

15. The method for suppressing mold deformation according to claim 1 or 2, wherein: The content of the inorganic binder layer is 1 part by mass or more and 7 parts by mass or less relative to 100 parts by mass of the refractory aggregate in the inorganic coated sand.

16. The method for suppressing mold deformation according to claim 1 or 2, wherein: The content of the inorganic binder in the inorganic binder layer is 15 mass % or more and 60 mass % or less.

17. The method for suppressing mold deformation according to claim 1 or 2, wherein: The inorganic binder layer contains amorphous silicon dioxide.

18. An inorganic coated sand comprising a refractory aggregate and an inorganic binder layer formed on the surface of the refractory aggregate, wherein: The inorganic binder contains at least one selected from sodium silicate and sodium metasilicate, and the inorganic binder layer contains a calcium compound, and the Ca content in the inorganic binder layer is 3% by mass or more and 45% by mass or less relative to all components in the inorganic binder layer except water, The calcium compound contains a Ca salt of an inorganic compound, The Ca salt of the inorganic compound is one or more Ca salts selected from the group consisting of calcium oxide, calcium carbonate, calcium silicate, calcium sulfate, calcium nitrate and calcium phosphate.

19. The inorganic coated sand according to claim 18, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 15-85:5-75:10-80.

20. The inorganic coated sand according to claim 18 or 19, wherein: The total content of the sodium silicate and the sodium metasilicate in the inorganic binder is 80 mass % or more.

21. The inorganic coated sand according to claim 18 or 19, wherein: The content of the Ca salt of the inorganic compound in the calcium compound is 80% by mass or more.

22. The inorganic coated sand according to claim 18 or 19, wherein: The solubility of the calcium compound in water at 20° C. is 0.001 g / L or more and 10 g / L or less.

23. The inorganic coated sand according to claim 18 or 19, wherein: The content of the inorganic binder layer is 0.05 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the refractory aggregate in the inorganic coated sand.

24. The inorganic coated sand according to claim 18 or 19, wherein: The Ca content in the inorganic binder layer is 3% by mass or more and 35% by mass or less relative to all components excluding water in the inorganic binder layer.

25. The inorganic coated sand according to claim 18 or 19, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 15-77:13-75:10-72.

26. The inorganic coated sand according to claim 18 or 19, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 20-70:20-70:10-60.

27. The inorganic coated sand according to claim 18 or 19, wherein: The molar ratio of Na:Ca:Si in the inorganic binder layer is 22-62:28-68:10-50.

28. The inorganic coated sand according to claim 18 or 19, wherein: The total content of the sodium silicate and the sodium metasilicate in the inorganic binder is 95% by mass or more.

29. The inorganic coated sand according to claim 18 or 19, wherein: The calcium compound is one or more selected from the group consisting of calcium oxide, calcium carbonate, calcium silicate, calcium sulfate, calcium nitrate and calcium phosphate.

30. The inorganic coated sand according to claim 18 or 19, wherein: The content of the Ca salt of the inorganic compound in the calcium compound is 95% by mass or more.

31. The inorganic coated sand according to claim 18 or 19, wherein: The solubility of the calcium compound in water at 20° C. is 0.005 g / L or more and 3 g / L or less.

32. The inorganic coated sand according to claim 18 or 19, wherein: The content of the inorganic binder layer is 1 part by mass or more and 7 parts by mass or less relative to 100 parts by mass of the refractory aggregate in the inorganic coated sand.

33. The inorganic coated sand according to claim 18 or 19, wherein: The content of the inorganic binder in the inorganic binder layer is 15 mass % or more and 60 mass % or less.

34. The inorganic coated sand according to claim 18 or 19, wherein: The inorganic binder layer contains amorphous silicon dioxide.

Citation Information

Patent Citations

  • JP1978025803B2

  • Coated sand, method for producing same, and method for producing casting mold using same

    WO2018097180A1

  • Mold material composition and method for producing mold using same

    WO2018147419A1

  • Excellent-combination-property precoated sand for hot method and preparation method thereof

    CN104841860A

  • Coated sand production method, coated sand obtained by the same, and cast production method

    JP2014117740A